Examining the expectations of early years' teachers in the U.A.E. regarding a successful start to school for children with and without special educational needs. Issue 4 (11th March 2020) - Takriti, Rachel A.; Elhoweris, Hala; Atkinson, Susan J.
ABSTRACT: Starting school has been shown to correlate with later school outcomes. The success of the transition of special educational needs (SEN) pupils depends on the child's adaptation to the new environment and on the teachers and school supports to facilitate learning. Previous research indicates that expectations of teachers toward pupils with SEN have been low. The aim of this study was to examine Early Years teachers' expectations with respect to the transition experience of children with Downs Syndrome and those without SEN in the U.A.E. Teachers working in the U.A.E. in Early Years' education completed a questionnaire twice, once thinking about their expectations of a child without any SEN and once thinking about a child with Downs Syndrome. Findings demonstrated a different pattern of expectations depending on whether the child had Downs Syndrome or no SEN, indicating, in general, a lower set of academic expectations for children with Downs Syndrome.